Effects of alpha-synuclein post-translational modifications on metal binding - González, Nazareno (2019)
Parkinson’s disease is the second most common neurodegenerative disorder worldwide. Neurodegeneration in this pathology is characterized by the loss of dopaminergic neurons in the substantia nigra, coupled with cytoplasmic inclusions known as Lewy bodies containing α-synuclein. The brain is an organ that concentrates metal ions, and there is emerging evidence that a break-down in metal homeostasis may be a critical factor in a variety of neurodegenerative diseases. α-synuclein has emerged as an important metal-binding protein in the brain, whereas these interactions play an important role in its aggregation and might represent a link between protein aggregation, oxidative damage, and neuronal cell loss. Additionally, α-synuclein undergoes several post-translational modifications that regulate its structure and physiological function, and may be linked to the aggregation and/or oligomer formation. This review is focused on the interaction of this protein with physiologically relevant metal ions, highlighting the cases where metal-AS interactions profile as key modulators for its structural, aggregation, and membrane-binding properties. The impact of α-synuclein phosphorylation and N-terminal acetylation in the metal-binding properties of the protein are also discussed, underscoring a potential interplay between PTMs and metal ion binding in regulating α-synuclein physiological functions and its role in pathology.